Expressing Well-Being Online: Towards Self-Reflection and Social Awareness - André, Paul; schraefel, m.c.; Dix, Alan; White, Ryen W. (iConference 2011, February 8-11, 2011, Seattle, WA, USA, 2011)
Medicine, psychology and quality of life literature all point to the importance of not just asking ‘how are you?’, but assessing and being aware of self and others’ well-being. Social networking has been shown to have a variety of uses and benefits, but does not currently offer explicit expression of a well-being state. We developed and deployed Healthii, a social networking tool to convey well-being using a set of pre-defined discrete categories. We sought to understand how communicating this in a lightweight fashion may be used and valued. Using a hybrid methodology, over five weeks ten participants used the tool on Facebook, Twitter, or on the desktop, and in group meetings discussed the affect and effect of the tool, before a final individual survey. The trial showed that participants used and valued status expression for its support to convey state, and for self-reflection and group awareness. We discuss these findings as well as future opportunities for awareness visualization and automatic data integration.